FROM ACADEMIC PROFICIENCY TO RELIGIOUS AFFILIATION: THE IMPACT OF SCHOOL ZONING POLICIES ON STUDENT DIVERSITY - Hendrik, Herman; W. Nurrochsyam, Mikka; P. Putra, Romeyn; Murdiyaningrum, Yunita (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2024)
Zoning-based New Student Admission is a policy designed to allocate students to schools based on their area of residence. This policy aims to ensure equitable access to education and promote social diversity within the school environment. This paper investigates the impact of the zoning-based New Student Admission system on student diversity in schools. The school zoning policy has the potential to modify the levels and dimensions of student diversity. Schools are required to admit the largest quota of students through the zoning route, resulting in a student body that reflects the composition of the local community. This research is significant because previous studies have primarily focused on administrative and academic aspects. Employing a qualitative methodology, including online focus group discussions (FGDs) as a data collection technique, this study found that schools labeled as